Risk factors of intracranial hemorrhage after mechanical thrombectomy of anterior circulation ischemic stroke - Neuberger, Ulf; Vollmuth, Philipp; Schönenberger, Silvia; Schieber, Simon; Ringleb, Peter A.; Bendszus, Martin; Pfaff, Johannes; Möhlenbruch, Markus Alfred (Neuroradiology, 2019)
PurposeIntracranial hemorrhage (ICH) is a potentially severe complication after mechanical thrombectomy (MT). Here, we investigated risk factors for the occurrence of any and symptomatic ICH after MT due to large-vessel occlusion of the anterior circulation.MethodsConsecutive patients with acute ischemic anterior circulation stroke with large-vessel occlusion undergoing MT were analyzed. ICH was categorized according to the Heidelberg Bleeding Classification. Forty-three procedural and clinical parameters were analyzed using univariate tests and multivariate logistic regressions.ResultsOf 612 patients, any ICH was detected in 195 (31.9%), while 27 (4.4%) developed a symptomatic ICH. Infarct size > 1/3 of vascular territory in control imaging (OR 2.18, 95% CI 1.45-3.21), higher serum glucose levels (OR 1.23 for change of 15 units mg/dL, 95% CI 1.10-1.39), and higher thrombectomy maneuver count (OR 1.21, 95% CI 1.11-1.32) were significantly associated with a higher risk of developing any ICH compared to no ICH. Wake-up strokes (OR 3.99, 95% CI 1.38-11.60), transfer from an external clinic (OR 3.04, 95% CI 1.24-7.48), and higher serum glucose levels (OR 1.22 for change of 15 units mg/dL, 95% CI 1.05-1.42) were revealed as independent risk factors for development of symptomatic ICH compared to no symptomatic ICH. Patients with no infarct demarcation (OR 0.10, 95% CI 0.01-0.80) and complete recanalization (OR 0.57, 95% CI 0.37-0.86) showed a lower risk of developing any ICH.ConclusionWake-up strokes and patients who are treated within a drip-and-ship concept are especially vulnerable for symptomatic ICH, while complete recanalization, contrary to subtotal recanalization only, was revealed as a protective factor against ICH.
Published online: 18 February 2019
Gesehen am 08.05.2019